Herbal spices as alternative antimicrobial food preservatives: An update - Chattopadhyay, R.R.; Bhattacharyya, S.K. (Pharmacognosy Reviews)
In recent years, there has been a constant search for alternative and efficient agents for food preservation aiming a partial or total replacement of antimicrobial chemical additives. A large number of herbal spices have been examined for their inhibitory action against the microorganisms responsible for food spoilage and foodborne illnesses. It has been reported by several researchers that natural antimicrobial and antioxidant properties of herbal spices reduce the risk of bacteria and fungi in foods and play a key role for enhancing shelf-life of foods and controlling food pathogens. Instead of these substantial findings, spices are still branded almost purely as flavoring agents. Recent research on antimicrobial and antioxidant activities of spices forms the basis for its application in raw and processed food preservation. It is now considered as a promising source of unique natural products to elucidate alternative food preservatives. This review gives a bird’s eye view mainly on the recent research on antimicrobial potential of herbal spices and their derivatives against some pathogenic and spoilage microorganisms in foods, their antioxidant activities along with possible adverse effects and advocates for more research to elucidate their commercial utilization in food preservation.
Keywords: Spices and derivatives; Antimicrobial activity; Antioxidant activity; Possible adverse effects; Alternative food preservatives